2019
DOI: 10.1093/ije/dyz230
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to chronic ionizing radiation increases risk of Parkinson's disease incidence in Russian Mayak workers

Abstract: Background Patients receiving radiotherapy demonstrate cognitive deficits, impairment of neurogenesis and neurovascular damage developing as late side effects of radiation exposure to the head. In light of the increasing use of diagnostic radiological procedures, epidemiological data raise concerns about possible harmful effects of low-level radiation on the human brain. A series of studies of chronically exposed Russian nuclear workers have provided information on risks of cancer and non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…A larger sample size of the pooled analysis would allow us to conduct more in-depth analyses of these outcomes as well as present an unparalleled opportunity to directly evaluate radiogenic risks of non-Hodgkin lymphoma and nonmalignant respiratory, cardiovascular, and renal diseases, which have been evaluated in studies of nuclear workers but have not been analyzed previously in uranium processing workers. Further, large-scale population studies are urgently needed to measure the potential radiation risks of AD, dementia, and other neurodegenerative disorders, such as, for example, the recently reported results for Parkinson's disease (Azizova et al 2020); see also (Boice 2017(Boice , 2019. One of the major concerns of NASA in space missions to Mars is the effect of high-LET radiation on brain tissue and the possibility of cognitive dysfunction and dementia related to long-term missions (Cekanaviciute et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger sample size of the pooled analysis would allow us to conduct more in-depth analyses of these outcomes as well as present an unparalleled opportunity to directly evaluate radiogenic risks of non-Hodgkin lymphoma and nonmalignant respiratory, cardiovascular, and renal diseases, which have been evaluated in studies of nuclear workers but have not been analyzed previously in uranium processing workers. Further, large-scale population studies are urgently needed to measure the potential radiation risks of AD, dementia, and other neurodegenerative disorders, such as, for example, the recently reported results for Parkinson's disease (Azizova et al 2020); see also (Boice 2017(Boice , 2019. One of the major concerns of NASA in space missions to Mars is the effect of high-LET radiation on brain tissue and the possibility of cognitive dysfunction and dementia related to long-term missions (Cekanaviciute et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Intakes of radionuclides may be capable of reaching the brain and exposing the tissue to low levels of alpha radiation (Leggett et al 2019). There are recent suggestions that ionizing radiation, primarily gamma radiation, leads to the development of neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease and dementia (Begum et al 2012;Azizova et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Countermeasures for extreme irradiation conditions (unfractionated doses above 2 Gy) have been extensively reported even though they present limited relevance for human CNS protection. Such doses can be emitted in the event of nuclear emergencies (Chernobyl 2002;Wong et al 1993) and in nuclear facilities (Gillies et al 2017;Azizova et al 2020)), but also in novel radiotherapy treatments, such as gamma knife surgery (Colaco et al 2016;Hasegawa et al 2017). They are referenced in this review as potential directions for future applications targeting more relevant radiation types and doses, with the assumption that some protective pathways might be extended across ranges of irradiation conditions (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…1 Reportedly, well water consumption, farming, smoking, pesticides, rural living, diet, and coffee and alcohol consumption as well as ionizing radiation, head trauma, and infections are the potential environmental risk factors for PD. [2][3][4] Studies 1,2,3,4 have reported controversial results, but for the most part, they have confirmed the association between environmental factors and PD. 2 In most of the studies, smoking has been found to be negatively associated with PD.…”
mentioning
confidence: 99%
“…PD is very common in Iğdır province, and Metsamor nuclear reactor is located at a distance of approximately 16 km from this province. 4 We aimed to investigate farming, well water consumption, rural living, and pesticide exposure as potential risk factors for PD in elderly individuals of Iğdır province through a case-control study and through chemical analysis of the well water for nitrate, phosphate, and heavy metal levels.…”
mentioning
confidence: 99%